2017
DOI: 10.1016/j.jembe.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects of multiple stressors: An invasive oyster and nutrient enrichment reduce subsequent invasive barnacle recruitment

Abstract: 16Studies identifying interactions between biological invasions and other stressors have 17 generally focussed on quantifying their cumulative effects on mature species assemblages. In 18 benthic systems, however, early life history processes are key determinants of assemblage 19 structure and functioning. This study tested whether the presence of an invasive species 20 affected early life history processes of two common barnacle species and whether this was 21 affected by a second common stressor, nutrient en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…When ecological responses to environmental drivers interact—that is, when their combined effects are either significantly greater (synergistic; Sala & Knowlton, ) or less than (antagonistic; Crain et al, ) the sum of their individual effects—predicting their cumulative impacts remains a significant challenge. We found that effects of predators and our experimental perturbations on univariate ecosystem functions—community metabolism, the biomass of algae and grazers, and abundance of meso‐invertebrates—were generally additive (i.e., equal to the sum of the individual effects; Vye, Emmerson, Dick, & O'Connor, ). This suggests that interactions between multiple stressors may not be a pervasive phenomenon in marine systems (Halpern et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…When ecological responses to environmental drivers interact—that is, when their combined effects are either significantly greater (synergistic; Sala & Knowlton, ) or less than (antagonistic; Crain et al, ) the sum of their individual effects—predicting their cumulative impacts remains a significant challenge. We found that effects of predators and our experimental perturbations on univariate ecosystem functions—community metabolism, the biomass of algae and grazers, and abundance of meso‐invertebrates—were generally additive (i.e., equal to the sum of the individual effects; Vye, Emmerson, Dick, & O'Connor, ). This suggests that interactions between multiple stressors may not be a pervasive phenomenon in marine systems (Halpern et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the difference in stressor impacts for various life forms demands research with regard to multiple anthropogenic drivers across the range of life history stages (Vye et al, 2017). The early life stages of intertidal species are crucial for the structure and function of adult populations on rocky shores and should be taken into consideration when investigating the effects of anthropogenic drivers (Connell, 1985).…”
Section: Multiple Driver Interactions Under Climate Change and Their Influence On Rocky Intertidal Systemsmentioning
confidence: 99%
“…Environmental stressors such as warming, nutrient enrichment, and harvesting of top predators are not present in isolation and often combine in surprising ways that cannot be predicted from their individual impacts (Crain et al, 2008;Vye et al, 2015Vye et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%